Some Geometric Properties of Close- to- Convex Functions - Alhily, Shatha S. (Iraqi Journal of Science, 2024)
The objective of this paper is to present some geometric properties of the close to convex function f when f is an analytic, univalent self-conformal mapping defined in the open unit disk D=z∈C: |z|<1, and on the boundary of D. One of the goals of this work was determining the sharp bound for the function of form f(z)=z/(1-z)^2δ , 0<δ<1, when R(f^’/g^’ (w_1))≥-2+δ/w_1 , for a some w_1∈∂D And another, if f has angular limit at p∈∂D . Then the inequality |(f^’ (z))/(g^’ (z) )|≥(-(1-2δ))/2(1+ δ) is sharp with extremal functions f(z)=z/(1-z)^2δ , and g(z)=z/(1+z), where 0<δ<1. Finally, if f is extended continuously to the boundary of D , then | (f^’/g^’ )(p)|≥ |1-2δ|(|1-2δ|-2)/|p-δ | ; 0<δ<1.